Indirect methods for counting elephants in forest - Barnes, Richard (Pachyderm, 1993)
The two methods most frequently used for estimating forest elephant numbers, guesses and dung counts, are discuss. Other methods such as using infrasound calls are noted, but the paper focuses on improving methodology of dung counts. Journal Table of Contents notes title as ’of counting’, text notes ’for counting’.